2020
DOI: 10.1108/jsm-12-2018-0351
|View full text |Cite
|
Sign up to set email alerts
|

Ten lessons for qualitative transformative service researchers

Abstract: Purpose This paper offers key methodological insights for scholars new to qualitative transformative service research (TSR). Design/methodology/approach The paper offers ten lessons on conducting qualitative TSR that the authors have gleaned, across more than 30 years (combined) of qualitative inquiries and engagement with other scholars conducting and publishing what may be now termed TSR. Findings The key lessons of conducting qualitative TSR work include: displaying ethics in conducting and presenting q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 20 publications
0
45
0
Order By: Relevance
“…is study revealed the intrinsic mechanism that the essence of the experience economy was well-being. In the era of the experience economy, the focus of enterprise management has changed from products and services to providing customers with experience [2]. erefore, the great change confronted by marketing today is the emergence of experiential marketing.…”
Section: Eoretical Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…is study revealed the intrinsic mechanism that the essence of the experience economy was well-being. In the era of the experience economy, the focus of enterprise management has changed from products and services to providing customers with experience [2]. erefore, the great change confronted by marketing today is the emergence of experiential marketing.…”
Section: Eoretical Implicationsmentioning
confidence: 99%
“…Consumers are exposed to services provided by supermarkets, banks, hotels, and telecommunication institutions almost every day. However, the traditional service research mainly focuses on consumer satisfaction, loyalty, repurchase intention, and word-of-mouth communication as the outcome of services [1], thus ignoring the question of how the quality of consumer life, such as consumer wellbeing, is affected by services, [2,3]. Consumer well-being refers to consumer perception of the positive contribution of products or services in improving the quality of life [4] and has become an important element ensuring sustainable urban development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers must seize this moment to use and create novel mixed methods methodologies for addressing the current crisis and to inform future cataclysmic and catastrophic social changes as well. (p. 285) This article addresses the call for innovative and novel mixed methods research (Azzari & Baker, 2020;Dodds & Hess, 2020;Gretzel et al, 2020;Fell et al, 2020;Fetters & Molina-Azorin, 2020;Mars & Ball, 2016;McSweeney & Faust, 2019;Pauwels, 2010) through a discussion of how the pandemic required our research team to reevaluate and continuously adapt data collection plans of visitor learning and proenvironmental behavior change in a Canadian National Park between June and September 2020. This continual process of adaptation resulted in both novel and innovative approaches in mixed methods research.…”
mentioning
confidence: 99%